PO 129 - Considerações Anestésicas na abordagem laparoscópica da Hérnia de Morgagni no Adulto - Branco Maia, Joana; Guimarães, Diana; Amaral, Joana; Tena Guerrero, José (Journal of the Portuguese Society of Anesthesiology, 2023)
x